2021
DOI: 10.1186/s12906-021-03274-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, anti-inflammatory and antioxidant activities of Mahanintangtong and its constituent herbs, a formula used in Thai traditional medicine for treating pharyngitis

Abstract: Background Mahanintangtong is listed in the Thailand’s National List of Essential Medicines (NLEM). It is used to treat non-specific fevers and illnesses such as pharyngitis and chickenpox. In this study, we investigated the biological activities of the different medicinal plants used in the Mahanintangtong formula. Methods The plant materials were extracted by maceration and decoction. Antimicrobial activity, assessed by disc diffusion method, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…The subsequent investigation into apoptosis mechanisms demonstrated that DLEE induced apoptosis in A549 cells through the intrinsic pathway, as evidenced by the disruption of mitochondria membrane potential (ΔΨm) and activation of pro-apoptosis proteins, including cleaved-caspase-9, cleaved-caspase-3, and cleaved-PARP-1, while inhibiting anti-apoptotic proteins such as Bcl-2, Bcl-xl, and survivin. Previously recognized for various bioactivities, such as anti-malarial, anti-ulcer, anti-diabetic, and anti-inflammatory effects, D. loureirin has demonstrated high antioxidant activity [ 19 , 21 , 36 , 37 , 38 ]. However, this study represents the first report of D. loureiri extract exhibiting anti-cancer activities against non-small-cell lung cancer through the inhibition of cell proliferation and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent investigation into apoptosis mechanisms demonstrated that DLEE induced apoptosis in A549 cells through the intrinsic pathway, as evidenced by the disruption of mitochondria membrane potential (ΔΨm) and activation of pro-apoptosis proteins, including cleaved-caspase-9, cleaved-caspase-3, and cleaved-PARP-1, while inhibiting anti-apoptotic proteins such as Bcl-2, Bcl-xl, and survivin. Previously recognized for various bioactivities, such as anti-malarial, anti-ulcer, anti-diabetic, and anti-inflammatory effects, D. loureirin has demonstrated high antioxidant activity [ 19 , 21 , 36 , 37 , 38 ]. However, this study represents the first report of D. loureiri extract exhibiting anti-cancer activities against non-small-cell lung cancer through the inhibition of cell proliferation and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 1 g of A. pericarpium was powdered, soaked in 20 mL of 95% ethanol, vortexed using ultrasonic power 200 W at 30 °C for 1 h, and the resulting solution filtered to produce extract 4. These extracts were concentrated under vacuum with a rotary evaporator to produce around 30 ml of dense plasters, and the plasters were then freeze-dried [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…[1], [13], [16], [18], [19], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32] [33], [34], [35], [36], [37] [21], [38], [39] Figure 2. Utilization of patchouli oil in various applications.…”
Section: Excluded As Not a Research Articlementioning
confidence: 99%